Utilización de la metodología de gestión por procesos para el monitoreo de los procesos que se llevan a cabo en el departamento de distribución de una empresa de comunicación de prensa escrita en la ciudad de Guayaquil - Aquiño, Evelyn (2009)
In the Distribution Department an important is realized, so they are the management of preparing the product an distribute it; taking decisions about the order of office, establishing routes and other actions that help to place at early hours of the morning the product on the market, in order that it could be acquired by clients and readers. Due to the fact that there exist processes to which a system of monitoring has not been established, it was decided to be employed on it and to implement the Methodology of Management for Processes, for which it developed a system that allows to measure the performance of the department. There was had access to historical information thanks to the help provided by the Chief and personal that works in this department, in addition information was compiled for one month to be able to analyze better the labors that intervene in this department.